2019
DOI: 10.5194/bg-2019-71
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable isotope signatures of Holocene syngenetic permafrost trace seabird presence in the Thule District (NW Greenland)

Abstract: Abstract. Holocene permafrost from ice wedge polygons in the vicinity of large seabird breeding colonies in the Thule District, NW Greenland, was drilled to explore the relation between permafrost aggradation and seabird presence. The latter is reliant on the presence of the North Water (NOW) polynya in the northern Baffin Bay. The onset of peat accumulation associated with the arrival of little auks (Alle alle) in a breeding colony at Annikitisoq north of Cape York is radiocarbon-dated to 4400 cal yr BP. A th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Here, the arrival of little auks, and with them large quantities of MDN, transformed nutrient availability, prompting a period of exceptionally high terrestrial and aquatic biological productivity. This is demonstrated by the fact that 2 m of peat accumulated in the catchment adjacent to the lake in just 1000 years, following little auk colonisation 65 , and the extremely high LOI values recorded in the lake (75% instead of <10% as expected for a High Arctic lake). Therefore, in addition to the large input of marine-derived cholesterol, there was also the input of cholesterol of terrestrial and freshwater origin, which has a higher proportion of β-sitosterol.…”
Section: Sea Ice Biomarkersmentioning
confidence: 91%
“…Here, the arrival of little auks, and with them large quantities of MDN, transformed nutrient availability, prompting a period of exceptionally high terrestrial and aquatic biological productivity. This is demonstrated by the fact that 2 m of peat accumulated in the catchment adjacent to the lake in just 1000 years, following little auk colonisation 65 , and the extremely high LOI values recorded in the lake (75% instead of <10% as expected for a High Arctic lake). Therefore, in addition to the large input of marine-derived cholesterol, there was also the input of cholesterol of terrestrial and freshwater origin, which has a higher proportion of β-sitosterol.…”
Section: Sea Ice Biomarkersmentioning
confidence: 91%
“…The radiocarbon dating and age-depth modeling could be describe more detail. I know, that it was a topic of paper by Davidson et al 2018, but still I have some doubts: Some samples for dating were collected from significantly thick core segments (even 10 cm long for topmost part of SI 1). Do author consider depth uncertinity in age-depth models?…”
mentioning
confidence: 99%
“…Therefore depth uncertainty in the age-depth models is of minor relevance for the present core records. The complete presentation of the agedepth models from Davidson et al (2018) can be found as Supplementary Material here: https://static-content.springer.com/esm/art%3A10.1007%2Fs13280-018-1031-1/MediaObjects/13280_2018_1031_MOESM1_ESM.pdf Please give some details on geological settings. According to my knowlage, at least in Saunders Is there is a lot of carbonate rocks.…”
mentioning
confidence: 99%
See 1 more Smart Citation